Development of teacher professionalism towards 21st century learning: Pembangunan profesionalisme guru ke arah pembelajaran abad ke-21 - Norazlinda Saad; Surendran Sankaran (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to identify the effect of Relevance and Conformity on Acceptance of the T3P Module (Technology, Pedagogy, Psychology, Assessment). This study is in a descriptive form using the review method. The population of this study is the National Middle School (SMK) teachers in the North Zone. As many as 60 teachers were selected as the study sample using the purposive sampling. The T3P module and search questions are used as study instruments. The research question is adapted from independent studies and literature reviews. The results of the pilot study showed a high Cronbach Alpha value (0.90). The collected data were analyzed using descriptive statistics and regression. The study results show that the Relevance and Conformity variables have a significant effect on the Acceptance of the T3P Module. The result of the study implies that the modules for Teacher Professionalism Development based on Lifelong Learning need to be reproduced to increase the potential and self-competence of teachers and strengthen the quality of state education.